2001
DOI: 10.1006/aphy.2000.6118
|View full text |Cite
|
Sign up to set email alerts
|

Casimir Effect: The Classical Limit

Abstract: We analyze the high temperature (or classical) limit of the Casimir effect. A useful quantity which arises naturally in our discussion is the ``relative Casimir energy", which we define for a configuration of disjoint conducting boundaries of arbitrary shapes, as the difference of Casimir energies between the given configuration and a configuration with the same boundaries infinitely far apart. Using path integration techniques, we show that the relative Casimir energy vanishes exponentially fast in temperatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 113 publications
8
105
0
Order By: Relevance
“…It was shown that the dielectric permittivity of the plasma model leads to small thermal corrections to the Casimir pressure at short separations in qualitative agreement with the case of ideal metals. At large separations it leads to the same result as for ideal metals in accordance to the classical limit [73,74].…”
Section: As Well]supporting
confidence: 66%
“…It was shown that the dielectric permittivity of the plasma model leads to small thermal corrections to the Casimir pressure at short separations in qualitative agreement with the case of ideal metals. At large separations it leads to the same result as for ideal metals in accordance to the classical limit [73,74].…”
Section: As Well]supporting
confidence: 66%
“…As in [17], this amounts to subtracting the diagonal contributions to the determinant which are not sensitive to the distance between the bodies (i.e., only contributes to their self-energies). This yields…”
mentioning
confidence: 99%
“…Since all polarizabilities (8), (9) or (24) are proportional to the transition frequency, the S z transitions connecting identical states do not contribute and we obtain the result of Eq. (32).…”
Section: Appendix B: Magnetic Transition Matrix Elementsmentioning
confidence: 78%